Bridging the Gap: Young Adult’s Need and Stakeholder’s Ability to Provide Health Information in Indonesia and Australia - Nurmala, Ira; Harris, Neil; Salim, Lutfi Agus; Muthmainnah, Muthmainnah; Devi, Yuli Puspita; Nadia, Asma (Journal of Ecohumanism, 2025)
This study aimed to investigate the health information desired by young adult and health education that has been carried out by stakeholders. The research method was quantitative and cross sectional. Data collection was carried out online through a survey monkey. The total number of respondents for this study was 529 students. The result showed that majority of young adults in Indonesia wish to know more about nutrition and healthy eating, while the majority of young adults in Australia want to know more about mental health. Health education to young adults was more effective through social media. One of the health education methods used by stakeholders was outreach, seminars and peer training. However, to facilitated the need for information through online platform, stakeholders faced challenges were varied.